1995
DOI: 10.1029/94wr02973
|View full text |Cite
|
Sign up to set email alerts
|

A Land Cover‐Based Snow Cover Representation for Distributed Hydrologic Models

Abstract: A snow cover depletion curve (SDC) summarizes the relationship between snow cover distribution and an average snow cover property, such as depth or water equivalent, for a given area. Snow cover depletion curves have been developed for, and applied in, hydrological models on a watershed or elevation zone basis. However, land cover-based SDCs are not prominent in the literature. For this study the areal distribution of snow cover for dominant land cover units was measured during the winters of 1991 and 1992 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 13 publications
1
78
0
Order By: Relevance
“…A scheme of Liston (SSNOWD, 2004) is used to describe the subscale snow heterogeneity in regional scale models (the equations used here can be found in the Appendix II). The model is based on two basic assumptions that are supported by many studies over the last decades (Donald et al 1995;Marks et al 1999;Faria et al 2000;Liston 2004). First, the spatial distribution of the snow cover is persistent and can be seen as approximately similar over the years ( fig.…”
Section: Model Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A scheme of Liston (SSNOWD, 2004) is used to describe the subscale snow heterogeneity in regional scale models (the equations used here can be found in the Appendix II). The model is based on two basic assumptions that are supported by many studies over the last decades (Donald et al 1995;Marks et al 1999;Faria et al 2000;Liston 2004). First, the spatial distribution of the snow cover is persistent and can be seen as approximately similar over the years ( fig.…”
Section: Model Formulationsmentioning
confidence: 99%
“…Liston (1999) found that the internal grid cell snow water equivalent distribution, the average According to Donald et al (1995), Pomeroy et al (1998) and Faria et al (2000), snow water equivalent depth distributions can be approximated by a two parameter log-normal Distribution parameter ξ: CV = coefficient of variation (Donald et al 1995) The average SWE depth of a grid cell D a under assumption of a certain melt depth D m is given by Donald et al (1995): Figures65a and 66 can be used to explain the operation of the presented routine. Figure 65a shows different log-normal functions which are representative for the sub-scale snow distribution of a grid element of e.g.…”
Section: Ii) Equations Used For the Subscale Snow Model Used In Chaptmentioning
confidence: 99%
See 1 more Smart Citation
“…WATCLASS uses land-cover based snow depletion curves (SDC) where the y-axis corresponds to average snow depth for the land-class and the x-axis represents SCA. The approach is outlined in more detail in Donald et al (1995). The land-class dependence of the SDC assumes that each land-class has a characteristic depth at which bare ground begins to appear during snowmelt.…”
Section: B Model Calibrationmentioning
confidence: 99%
“…This routine is developed under the assumptions that precipitation as snow is lognormally distributed in space with a fixed coefficient of variation. Donald et al (1995) presented a snow accumulation model where, once the snow coverage was 100%, the spatial variability of SWE remained constant. These static ways of representing the spatial distribution of SWE are thus in conflict with the central limit theorem, reported observations Pomeroy et al, 2004) and observations presented in this paper.…”
Section: Introductionmentioning
confidence: 99%